THE EXSISTENCE OF HUMAN RIGHTS IN INDONESIA - Ahmad Zaini; Mohammad Zainor Ridho; Entol Zaenal Muttaqin (Jurusan Hukum Tata Negara, Fakultas Syariah, UIN Sultan Maulana Hasanuddin Banten, 2020)
Human rights are fundamental rights, namely the basic rights possessed by humans that they carry since they are born that are related to their dignity and dignity as the creation of God Almighty, so that their existence is a necessity, cannot be contested, even must be balanced, respected and maintained from all kinds of threats, obstacles and disturbances from other humans. Because human rights are basic human rights or basic rights that have been born as a gift from God Almighty, this right is very basic in nature and human life which is very natural, that is, it cannot escape from and in human life. As a legal state, in the elaboration of human rights, the Indonesian state refers to the Pancasila and the 1945 Constitution. The Pancasila perspective and the 1945 Constitution on human rights must be carried out as a system which includes the movement of state life which is not only interdependent but also contribute to each other.